Effect of isokinetic muscle strength training on knee muscle strength, proprioception, and balance ability in athletes with anterior cruciate ligament reconstruction: a randomised control trial - Wang, Kun; Cheng, Liang; Wang, Bingcheng; He, Benxiang (Frontiers in Physiology, 2023)
Objective: This study aimed to investigate the effect of regular isokinetic muscle strength training on the knee muscle strength, proprioception and balance ability in athletes after anterior cruciate ligament (ACL) reconstruction.Methods: Forty-one athletes who underwent ACL reconstruction were randomly divided into the experimental (n = 21) and control (n = 20) groups. The experimental group used an isokinetic muscle strength tester for 4 weeks (5 times/week) of knee flexion and extension isokinetic muscle strength training. The control group used the